Introduction: New Dynamics of Chinese Migration to Europe. (29th May 2020) - Thunø, Mette; Li, Minghuan
Abstract: This introduction provides a presentation of the articles in this special issue by framing the contributions in the context of new dynamics related to Chinese migration studies and the ongoing discussions of the impact of China's powerful economic position. The articles offer new empirical insights to develop new understandings of recent migration and mobilities between China and Europe. By focusing on the changing socio‐economic composition of Chinese migrants in Europe towards highly skilled professionals and investors, changes in Chinese entrepreneurship, increasing Chinese political engagement and activism, and new migration from Europe to China by Chinese descendants, these contributions reflect the importance of developing new theories to better grasp the causes and effects of China's new global economic and political position for Chinese migration. The selected articles identify promising directions for future work on the global discussions of the impact of China as a diaspora state and ensuing policy implications.